2012
DOI: 10.1111/j.1755-5949.2012.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Carnosine on Subcortical Ischemic Vascular Dementia in Mice

Abstract: These data suggest that the neuroprotective effect of carnosine on rUCCAO in mice is not dependent on the histaminergic pathway, but may be due to a suppression of reactive oxygen species generation, glia activation, and myelin degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 45 publications
1
58
1
Order By: Relevance
“…Several previous reports showed that carnosine also had beneficial activities in neurodegenerative diseases including Alzheimer diseases, 61 and dementia. 62 Of note, dysregulation of autophagic processes have been recently recognized to contribute to the progress of these neurodegenerative diseases. 63,64 Further elucidation of carnosine's effects on autophagy in these neurodegenerative diseases is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports showed that carnosine also had beneficial activities in neurodegenerative diseases including Alzheimer diseases, 61 and dementia. 62 Of note, dysregulation of autophagic processes have been recently recognized to contribute to the progress of these neurodegenerative diseases. 63,64 Further elucidation of carnosine's effects on autophagy in these neurodegenerative diseases is needed.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57] In mice treated with right unilateral common carotid arteries occlusion (rUCCAO), an animal model for SVID, microglia in the corpus callosum were also found to be activated as the number of ionizing calcium-binding adaptor molecule 1 (Iba-1) positive microglia was greatly increased. 58 Treatment of carnosine (β-alanyl-L-histidine), a natural dipeptide highly expressed in CNS, resulted in microglial deactivation and ameliorated cognitive impairment and white matter lesion in these mice. These results also support that early classical activation of microglia contributes to demyelination at the early stages of white matter diseases.…”
Section: Iver S E Ac Tivati On Of MI Crog Lia In White Mat Ter-rementioning
confidence: 99%
“…Recent research showed that carnosine reduces brain damage after ischemic stroke by preserving the normal glutathione levels and decreasing matrix metalloproteinase levels and activity36. Furthermore, carnosine can suppress myelin degeneration in mice after unilateral common carotid arteries occlusion37. Therefore, given that CEGI contains both these components, CEGI might be more potent and effective than either component alone.…”
Section: Discussionmentioning
confidence: 99%